Serotonin syndrome in the acute treatment landscape of migraine: the lasmiditan experience - Blumenfeld, Andrew; Tepper, Stewart J.; Khanna, Rashna; Doty, Erin; Vincent, Maurice; Miller, Sheila I. (Frontiers in Neurology, 2023)
Background Serotonin syndrome (SS) symptoms overlap with adverse events associated with lasmiditan, a 5-HT (serotonin)1F receptor agonist for acute treatment of migraine. Because SS symptoms are heterogeneous, diagnosis can be challenging, and potential cases observed with lasmiditan treatment led to questions about SS pathophysiology. Here, we provide an overview of the potential risk of SS based on experience with lasmiditan. Methods Results of eight phase 2 and phase 3 lasmiditan trials (n = 5,916) and a controlled intravenous trial of lasmiditan (n = 88) were analyzed for symptomatology consistent with SS. Post-marketing surveillance data from lasmiditan’s US launch date (January 2020) until data cut-off (April 2021) were also examined. Established Sternbach and Hunter diagnostic criteria were used for formal determination of SS. Results Of 6,004 lasmiditan-treated clinical trial patients, 15 reported ≥1 treatment-emergent adverse event consistent with signs and symptom(s) of SS. After review, one case met Sternbach and Hunter criteria, two cases potentially met Sternbach criteria, and three cases reported as SS had limited/no information to determine if either criterion was met. During post-marketing surveillance (approximately 13,400 lasmiditan prescriptions), 17 cases with symptom complexes consistent with SS were reported; 3/17 cases had adequate case descriptions to apply predefined criteria. Of these, two met Sternbach and Hunter criteria, and one met Sternbach criteria. Conclusion Awareness of clinical symptomatology and diagnostic criteria of SS can help clinicians with recognition of rare instances of SS that may occur with lasmiditan. Clinical trial registration NCT03670810, NCT00384774, NCT00883051, NCT02565186.